The effect of sintering temperature on characteris-tic and properties of hydroxyapatite extracted from fish scale bio-waste - ALIAS, MASLINDA; HAMZAH, SOFIAH; SAIDIN, JASNIZAT (International Journal of Engineering and Technology, 2018)
This present study focused on the extraction of HAp from fish scale waste using alkaline heat treatment sintered at different sintering tem-perature (high range) between 300Â° C to 1000Â°C. White powder hydroxyapatite was characterized in term of morphology, surface chemistry and crystallinity structure using Scanning Electron Microscopy, Fourier transform infrared spectroscopy (FTIR) and X-ray Diffraction (XRD), respectively. Analysis from XRD shows that FSHAp-1000 has good sharp peak indicating for high crystallinity of hydroxyapatite. While, the functional analysis performed FTIR determined several functional group attributed to PO42-, CO23- and OH-. As sintering tem-perature increase, the broad peak of PO42- becomes narrower. The intensity of CO32- is observed decreased at higher calcination temperature since they are release as volatile gases. Meanwhile, adsorbed water become narrower under treatment of water. The morphology of FSHAp changed upon treatment of heat especially at high temperature. As sintering temperature increase, the particle size of FSHAp becomes fines and a regular shape of FSHAp was found agglomerated.